Answer:
(f - g)(x) = 2x - 3
Step-by-step explanation:
(f - g)(x) is defined as subtracting the whole g(x) function from the f(x) function.
Hence, we can define it as:
(3x - 1) - (x + 2)
= 3x - x - 1 - 2
= 2x - 3
Therefore, (f - g)(x) = 2x - 3.
Hope this helped!
Answer:
In a paragraph proof, statements and their justifications are written in sentences in a logical order.
A two-column proof consists of a list statements and the reasons the statements are true.
A paragraph proof is a two-column proof in sentence form.
Step-by-step explanation:
- In a paragraph proof, statements and their justifications are written in sentences in a logical order.
- A two-column proof consists of a list statements and the reasons the statements are true.
- A paragraph proof is a two-column proof in sentence form.
A paragraph proof is only a two-column proof written in sentences. However, since it is easier to leave steps out when writing a paragraph proof.
A two-column geometric proof consists of a list of statements, and the reasons that we know those statements are true. The statements are listed in a column on the left, and the reasons for which the statements can be made are listed in the right column
2x-x-7=0
3x-7=0
add 7 to 7 and 0, so then we cross out 7-7, and then
3x=7, bc u change the subtraction to addition, sr if thst doesn't make sense but 3x=7 is the answer
Simplify the following:
(k^3 k^7)/3 - 5
Combine powers. (k^3 k^7)/3 = k^(7 + 3)/3:
k^(7 + 3)/3 - 5
7 + 3 = 10:
k^10/3 - 5
Put each term in k^10/3 - 5 over the common denominator 3: k^10/3 - 5 = k^10/3 - 15/3:
k^10/3 - 15/3
k^10/3 - 15/3 = (k^10 - 15)/3:
Answer: (k^10 - 15)/3
700 is what is half of that I think